Isolation, Characterization and Cytotoxicity of Phytochemicals from Sekobang Kechil (Anaxagorea Javanica) - Zakaria, Siti Mariam (2009)
Thirty-one plant extracts were obtained from the extract bank of Natural Product Laboratory, Institute of Bioscience, Universiti Putra Malaysia. The whole plant extracts were tested for cytotoxic effect on human breast cancer (MCF-7), prostate cancer (DU-145) and lung cancer (H-460) cell lines using MTT assay. The results of the preliminary cytotoxicity tests showed that eight extracts exhibited very strong activity against one or more of the cell lines at 100 μg ml-1, with cell viability of 10% or less. The methanolic extract of Anaxagorea javanica leaves exhibited the strongest activity against all three cell lines with cell viability of less than 2% and further dose-response tests against the MCF-7 cell line showed that it had an IC50 value of 2.4 μg ml-1. This sample was thus selected and recollected in larger quantities for further phytochemical investigation. The dichloromethane (DCM) fraction of the first collection was subjected to chromatographic purification from which a known flavonoid, 3',4',5-trihydroxy-3,7-dimethoxyflavone (41), was obtained. From the chromatographic separation of the DCM extract of the second collection batch, a mixture of long chain alkanes, predominated by nonacosane (42) and a mixture of stigmasterol (43) and β-sitosterol (40) were isolated, in addition to three pure phytochemicals, namely an aliphatic acid, hexadecanoic acid (44), and two alkaloids, 11-methoxyeupolauridine (45) and 4,11-dimethoxyeupolauridine (46). The latter two compounds were found to be new naphthyridine alkaloids with eupolauridine nuclei and reported for the first time for this species. Compounds that had been obtained in sufficient quantities were tested for cytotoxic activity against the MCF-7 cell line. The samples assayed were 3',4',5-trihydroxy-3,7-dimethoxyflavone (41), nonacosane (42), stigmasterol (43) and β-sitosterol (40) mixture, and 11-methoxyeupolauridine (45). Only 3',4',5-trihydroxy-3,7-dimethoxyflavone (41) showed cytotoxic effect with an IC50 value of 3.4 μM, and this was its first report for this activity. Plausible biogenetic pathways of the new compounds were also discussed.